Survival of patients with ruptured gastrointestinal stromal tumour treated with adjuvant imatinib in a randomised trial: clinical studies - Joensuu, Heikki; Reichardt, Annette; Eriksson, Mikael; Hohenberger, Peter; Boye, Kjetil; Cameron, Silke; Lindner, Lars H.; Jost, Philipp J.; Bauer, Sebastian; Schütte, Jochen; Lindskog, Stefan; Kallio, Raija; et al. (British journal of cancer, 2024)
Patients with ruptured gastrointestinal stromal tumour (GIST) have poor prognosis. Little information is available about how adjuvant imatinib influences survival.